Assessing the Management of the Reputational Component of Corporate Social Responsibility of Ukrainian Companies - Yevtushenko Viktoriia A. (Problemi Ekonomiki, 2021)
The article is aimed at assessing the corporate social responsibility of organizations in Ukraine by using progressive international ratings, defining the relationship and interaction of the social responsibility and reputation of a company, and on this basis at developing a conceptual scientific and methodological approach to assessing the corporate social responsibility of Ukrainian companies. Modern international methodological approaches to assessing the management of the reputational component of social responsibility are analyzed, namely, Global CR RepTrak and Net Promoter Score. The research carried out shows the lack of a qualitative methodology to assess the reputational component of corporate social responsibility in Ukraine. Using the methodology of Global CR RepTrak and Net Promoter Score, and having analyzed open information sources, data from various ratings of Ukrainian companies, and own observations, the author proves the actual value of assessing the reputational component of corporate social responsibility of domestic enterprises, and performs the assessment itself. It is substantiated that both the external and internal reputational components of corporate social responsibility should be used for managing any national organization effectively. A new method for assessing the reputational component of corporate social responsibility is suggested with a view to providing socially responsible management of Ukrainian companies. Further research is needed to: define a system of institutional forms of the social responsibility of domestic enterprises; develop CSR models of national business structures; create comprehensive scientific and practical methods that will unambiguously assess the CSR of Ukrainian enterprises and turn the social responsibility of national producers into a competitive resource asset in global markets.